The Oxford handbook of public choice. Volume 1 - Congleton, Roger D.; Grofman, Bernard; Voigt, Stefan (New York : Oxford University Press, 2019)
The two volume Oxford Handbook of Public Choice provides a comprehensive overview of the Public Choice literature. Volume 1 covers rational choice models of elections, interest groups, rent seeking, and public choice contributions to normative political economy. It begins with introductory chapters on rational choice politics, the founding of public choice, and the evaluation and selection of constitutions.
Rational Choice and Politics / Roger D. Congleton -- Spatial voting models of party competition in two dimensions / James F. Adams -- Spatial social choice / Norman Schofield -- Economic voting / Michael S. Lewis-Beck, Mary Stegmaier -- Valence politics / Haldun Evrenk -- The Study of Strategic Voting / André Blais, Arianna Degan -- Turnout: Why do voters vote? / Serguei Kaniovski -- Expressive voting / Alan Hamlin, Colin Jennings -- Altruism and political participation / Richard Jankowski -- Social Embeddedness and Rational Turnout / Carole Jean Uhlaner -- Information cues and rational ignorance / Shaun Bowler, Stephen P. Nicholson -- Choosing among Governments / Alan Hamlin -- Campaign Finance / Thomas Stratmann -- Primaries, conventions, and other methods for nominating candidates: How do they matter? / Gilles Serra -- Logrolling and coalitions / Anthony J. McGann -- Collective action / Jac C. Heckelman -- Rent Seeking: The resource cost of influence / Arye L. Hillman, Ngo Van Long -- The structure of contests and the extent of dissipation / Karl Wärneryd -- The Political Economy of Rent Creation and Rent Extraction / Roger D. Congleton -- Empirical evidence on rent seeking costs / Ignacio del Rosal -- 'The Bureaucracy' as an Interest Group / Patrick Dunleavy -- Interest groups and regulatory capture / William F. Shughart II, Diana W. Thomas -- Public Choice: Early Contributions / Dennis C. Mueller -- Corruption / Toke Aidt -- The Political Economy of Trust / Christian Bjørnskov -- Contested Political Persuasion / Stergios Skaperdas, Samarth Vaidya -- Stochastic Process Models of Preference Change / Michel Regenwetter, Yung-Fong Hsu -- Leadership as Persuasion / Benjamin E. Hermalin -- Public choice and social democracy / Peter Kurrild-Klitgaard -- Fairness concepts / Christian Klamler -- Social contract vs. Invisible hand: Agreeing to sol
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on February 5, 2019).
Keywords: Social choice